By the numbers. (Washington, D.C. : National Geographic Society, 2015)
"Did you know that your brain can hold 1 million gigabytes of data? (That's like 3 million hours of TV!) Get ready to be wowed by this awesome book of numbers! Boost your math brainpower with easily "getable" infographics that bring amazing stats, facts, and figures to life. Meet real-life experts who work with numbers every day. Plus, get tips and tricks on how to make your own awesome infographics!"--Back cover.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references (pages 240-243) and index.
Description based on print version record.
Keywords: Curiosities and wonders -- Juvenile literature; Statistics -- Juvenile literature; Mathematics -- Juvenile literature; Visual communication -- Juvenile literature; Communication -- Graphic methods -- Juvenile literature; Information visualization -- Juvenile literature; Curiosities and wonders; Electronic books- OSLIS; Statistics; Electronic books